Empirical findings on enhancing the well-being of poor people through Islamic transformation centre, network of mosque and entrepreneurship: a refined conceptual solution - Zakaria, Zyed; Ammar, Muhammad Afiq; Ismail, Lawal Adebayo; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2016)
The purpose of this paper is to gather some empirical finding from the previous paper which is about enhancing the well-being of poor people through Islamic Transformation Centre (ITC), Network of Mosque (NOM), entrepreneurship and Big Data. Stakeholder in this paper are plays a crucial role in enhancing the well-being of poor people. This paper focuses on poor people and how Islamic transformation Centre(ITC) and Network of Mosque (NOM) can improve their well-being. The stakeholders that are involved in this surveys are poor people, government, non-government agencies and also entrepreneurs. This paper is based on literature review, business model canvas (BMC), value proposition design (VPD) and environmental map (EM. A survey was designed and conducted with poor students that receive Zakat from IIUM by using snowball sampling method. In this paper there will have a refined BMC and VPD along with the survey result.